THE TETTIGONINAE OF THE ATLANTIC ISLANDS - BOLIVAR, J IGNACIO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1940)
The appearance of the larva in various stages of its growth is descr in detail
CIENC MEX
Keywords: TETTIGONINAE, ATLANTIC ISLANDS; MULTIDISCIPLINARIA; OCEANOGRAFIA; GEOLOGIA MARINA